Społeczności kultury późnej ceramiki wstęgowej centralnej części Wysoczyzny Kujawskiej - Żurkiewicz, Danuta (Folia Praehistorica Posnaniensia, 2018)
The paper discusses a structure of the settlement pattern of the Late Band Pottery culture – the Lengyel culture, Brześć Kujawski group, in a part of the Kujavia Plateau. In the first part, a microregional analysis of three selected sites is presented, in addition to discussing a special character of the associated artefacts. The second part focuses on the geography of settlement.